2014
DOI: 10.5664/jcsm.3970
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Comprehensive, Unattended Ambulatory Polysomnography in School-Aged Children

Abstract: Study Objectives: Although unattended ambulatory polysomnography (PSG) is frequently performed in adults, few studies have been performed in children. The objective of this study was to evaluate the feasibility of comprehensive, ambulatory PSG, including electroencephalography, in school-aged children in the home environment. Methods: A total of 201 children, born premature with birth weights of 500-1,250 grams, currently aged 5-12 years and living in Canada and Australia, underwent unattended ambulatory PSG. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 19 publications
6
73
3
Order By: Relevance
“…7 In brief, a subset of children enrolled in follow-up studies for the Caffeine for Apnea of Prematurity (CAP) trial 15,16 underwent 2-week actigraphy monitoring prior to a single night of comprehensive, ambulatory polysomnography. Polysomnography results are published elsewhere 7,17 and will not be reported here. Caregivers completed questionnaires relating to general sleep at the end of the 2-week actigraphy study.…”
Section: Etho Dsmentioning
confidence: 99%
“…7 In brief, a subset of children enrolled in follow-up studies for the Caffeine for Apnea of Prematurity (CAP) trial 15,16 underwent 2-week actigraphy monitoring prior to a single night of comprehensive, ambulatory polysomnography. Polysomnography results are published elsewhere 7,17 and will not be reported here. Caregivers completed questionnaires relating to general sleep at the end of the 2-week actigraphy study.…”
Section: Etho Dsmentioning
confidence: 99%
“…8,9 This technique, which uses sophisticated technology to assess brain, cardiovascular and respiratory activity during sleep usually in a laboratory environment, is expensive and labor-intensive and typically only provides one or two nights of information, which may not be reflective of sleep in the home. 10 Actigraphy, which use accelerometer technology to provide estimates of sleep and wake based on the level of activity, is used to provide objective assessments of sleep-wake patterns over long periods of time 11,12 and assist in diagnosis and treatment monitoring of sleep disorders such as delayed sleep phase syndrome and behavioral insomnia. 13 Validation studies in infants, children and adolescents have shown that actigraphy is sensitive in assessing actual sleep, however over-or underestimates wake after sleep onset, providing a poor estimate of sleep disruption when compared to PSG.…”
Section: Introductionmentioning
confidence: 99%
“…The data sets were then compared, which revealed that AHI was understated with the HSAT data set; this disparity could have significantly affected clinical management decisions in 23% of patients in the study, including 27.5% of patients with an AHI of 1 to 5 and 60% of patients with an AHI of 5 to 10. 22 In total these validation studies report data from 208 children in whom the gold standard of PSG was directly compared with HSATs for the diagnosis of OSA 9,10,[14][15][16][17][18] ; however, an HSAT was only performed at home in 2 of the studies. 18,19 Overall, these validation studies reported a relatively wide range of sensitivities and specificities that varied to some extent with severity of OSA.…”
Section: Validity Of Hsats In Childrenmentioning
confidence: 99%
“…More recently, Marcus and colleagues conducted a large multisite study to examine the clinical feasibility of HSATs to evaluate OSA in children. 15 This study included 201 children, ages 5 to 12 years, all with a history of prematurity. Technically acceptable studies were obtained on the first night in 91% of the children and 98% when an additional study was performed.…”
Section: Technical Feasibility Of Hsats In Childrenmentioning
confidence: 99%
See 1 more Smart Citation